Ecosystem Services and Border Regions. Case Study from Czech – Polish Borderland - Spyra, Marcin (TeMA - Journal of Land Use, Mobility and Environment, 2014)
Land-use management and planning of cross-border regions is a complex problem. Different legislatures, development visions and interests on both sides of the border make it even more complicated. Introducing ecosystem services concept into land-use planning and management at cross-border regions is a challenge. However not much is said about this issue in literature. This paper aims to present result of the study concerning to ecosystem services concept in the context of cross-border part of Pradziad Euroregion. The studyed area is situated within Czech – Polish borderland. First part of the research concerns to land-cover analyze of the region. The second one to Czech and Polish land-use strategies, which are binding at NUTS 4 and 5 level in the studyed area. Resoults of the research indicates asymmetry of the cross-border landscape of the analyzed region. The asymmetry is indicated by different types, biodiversities and areas of ecosystems identified on both sides of the border. It is also identified by differences in land-use strategies concerning to the region. It is discussed to what extend ecosystem services concept can be implemented in planning legislature of the cross-border region.